1969
DOI: 10.1002/oms.1210020308
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric studies of structural isomers—II: Mono‐and bicyclic C6H10 molecules

Abstract: The electron-impact-induced ionization and fragmentation of six CsHlo structural isomers have been studied in order to determine the effect of isomerism upon their mass spectrometric behavior. The 70 eV mass spectra, metastable transitions and appearance potentials of the principal 299 * R. E. Winters and J. H. Collins, unpublished results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
23
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 30 publications
13
23
0
Order By: Relevance
“…The reason for this discrepancy lies probably in a wrong calibration of the energy scale, since the cyclohexene ionization energy is itself overestimated by ∼0.6 eV in Praet's report. 18 More recently, Li and Baer 20 explored the behavior of cyclohexene by threshold photoelectron-photoion coincidence spectroscopy; they obtained AE values for both [C 5 H 7 ] + and [C 4 H 6 ] •+ within ∼0.1 eV of the results reported by Winters and Collins 17 and Traeger and Lossing. 19 It is essential to note that the differences between the appearance and ionization energies for methyl loss and ethylene loss, 119 17 -127 19 and 166 17 kJ/mol, respectively, are close to the enthalpy difference between the dissociation products and the cyclohexene molecule (Table 1).…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…The reason for this discrepancy lies probably in a wrong calibration of the energy scale, since the cyclohexene ionization energy is itself overestimated by ∼0.6 eV in Praet's report. 18 More recently, Li and Baer 20 explored the behavior of cyclohexene by threshold photoelectron-photoion coincidence spectroscopy; they obtained AE values for both [C 5 H 7 ] + and [C 4 H 6 ] •+ within ∼0.1 eV of the results reported by Winters and Collins 17 and Traeger and Lossing. 19 It is essential to note that the differences between the appearance and ionization energies for methyl loss and ethylene loss, 119 17 -127 19 and 166 17 kJ/mol, respectively, are close to the enthalpy difference between the dissociation products and the cyclohexene molecule (Table 1).…”
Section: Resultsmentioning
confidence: 74%
“…[17][18][19] As mentioned in the Introduction, methyl loss is the lowest energy pathway of the two competitive channels. Winters 17 By contrast, Praet, 18 who used the extrapolated voltage difference method, reported AE energies higher by ∼1.0 eV than the values reported by the preceding authors. The reason for this discrepancy lies probably in a wrong calibration of the energy scale, since the cyclohexene ionization energy is itself overestimated by ∼0.6 eV in Praet's report.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the AEs of the fragment ions investigated by EI technique, a considerable discrepancy was found. For example, the AE of C 3 H 5 + was determined to be 13.68 ± 0.05 eV by Praet, while Winters and Collins reported a value of 12.12 ± 0.12 eV . Recently, the near‐threshold absolute photoionization cross sections of cyclohexene was measured with photoionization mass spectrometry (PIMS) using a monochromated vacuum ultraviolet (VUV) synchrotron light source .…”
Section: Introductionmentioning
confidence: 99%
“…The thermochemistry of C6Hlo isomers has been investigated by Winters and Collins (22) and more recently by Lossing and Traeger (14). The latter authors conclusively showed that at threshold, the [C,M,]' daughter ion from cyclohexene has the [cy~lopentenium]~ structure; this they showed to be rhe most stable [C,H,]' ion, (AH, = 199 kcal mol-l) with [dimethylcyclopropenium] + as the probable nearest [C ,H7] ' isomer (AH,(estimated) = 217 kcal molF1).…”
Section: Introductionmentioning
confidence: 99%